التوزّع العمودي لمجذافيات الأرجل Copepoda و تغيّراتها النوعية و الكميّة خلال فصلي الصيف والشتاء في المنطقة الشاطئية لمدينة جبلة - الحنون كمال; حمامة ماجد (Latakia University Journal -Biological Sciences Series, 2013)
جرت عملية الاعتيان العمودي لمجذافيات الأرجل Copepoda خلال الصيف والشتاء بين عامي 2009 و2010 في منطقة قلعة الزوزو التي تقع في المنطقة الشاطئيّة لمدينة جبلة . التي تتميز بخواص بيئية مميزة، وترافق جمع العينات بقياس درجة حرارة الماء، الملوحة، والأوكسجين المنحل في الماء . بلغ العدد الإجمالي للعينات المدروسة في مناطق الدراسة جميعها 106 عيّنةً. تمّ تحديد100نوع خلال الصيف،بينما تمّ تحديد89 نوعاً خلال الشتاء، ينتمي معظم الأنواع إلى رتبة Calanoida. كما لوحظ من خلال الدراسة أنّ معظم الأنواع قد ظهرت في الفصلين معاً، بينما ظهر بعض الأنواع في فصلٍ دون الآخر. ولوحظ من الدراسة أنّ غزارة مجذافيات الأرجل كانت أعلى في فصل الصيف حيث بلغ متوسطها(5314 فرد/م3) ،بينما بلغ متوسطها في فصل الشتاء ( 4353,40فرد/م3). كما تبيّن من الدراسة أنّ المحطّة القريبة من الشاطئ كانت أقلّ تنوّعاً و أكثر غزارةً من المحطّة البعيدة عن الشاطئ فصلي الصيف والشتاء معاً. وتبيّن كذلك من الدراسة أنّ غزارة مجذافيات الأرجل في الطبقات المائية المختلفة خلال فصل الصيف كانت أعلى في الطبقة المائية (25-15) م من المحطة B القريبة من الشاطئ(1583,29فرد/م3)، أمّا في المحطة B`البعيدة عن الشاطئ والعميقة فقد كان متوسط غزارة مجذافيات الأرجل أعلى في الطبقة المائية (50-25) م (790,87فرد/م3) ، بينما كان متوسط غزارة مجذافيات الأرجل خلال فصل الشتاء أعلى في الطبقة المائية (25-15) م من المحطة B (1245,01 فرد/م3)، أمّا في المحطة B` فقد كان متوسط غزارة مجذافيات الأرجل أعلى في الطبقة المائية(50-25) م (751,33فرد/م3) . Vertical sampling process took place to Copepoda during the summer and winter of 2009 and 2010 from Alzzouzo castle which is located in the coastal region of Jableh city. This region has special environmental properties. Sampling was accompanied with measuring water temperature, salinity, and dissolved oxygen in the water. The total number of samples studied in all areas of study is 106 samples. 100 species were identified during the summer, while 89 species were identified during the winter; most species belongs to the order of Calanoida. It was noted by the study that most species appeared in two seasons together, while some species appeared in the season without the other. It was also noted that the abundance of Copepoda was higher in summer with an average of (5314 individual / m 3), while the average in winter was (4353, 40 individual / m 3). It was clear from the study that the station near the beach was less diverse and more prolific than the offshore station during the summer and winter together. The study showed that the abundance of Copepoda in different water layers during the summer were higher in water layer (25-15) m than the station B near the beach (1583,29 individual / m 3), while in the deep station B `offshore the abundance average of Copepoda was higher in the water layer (50-25) m (790,87 individual / m 3), while the abundance average of Copepoda was higher during the winter in the water layer (25-15) m than the station B (1245,01 individual / m 3), the station B the abundance average of Copepoda was higher in the water layer (50-25) m (751,33 individual / m 3).